2013
DOI: 10.1210/jc.2013-1460
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Fractures in Patients With Acromegaly: A 3-Year Prospective Study

Abstract: This prospective study demonstrates a high rate of incident vertebral fractures both in patients with active and controlled acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 53 publications
7
103
2
16
Order By: Relevance
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 72%
“…Recently, several studies have shown a marked increase in vertebral fracture prevalence and incidence for both sexes in acromegaly (5,31,32,33,34), related to the duration of disease activity and gonadal status among others. These observations underscore the complexity of a chronic and devastating disease as acromegaly, for bone as a target organ with fracture as the ultimate end point (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria from the study were: i) diagnosis of active neoplastic disease; ii) ongoing treatment with antiosteoporotic drugs with the exception of calcium and vitamin D supplements; iii) treatment with drugs causing osteoporosis with the exception of glucocorticoid replacement therapy in hypopituitaric patients; iv) clear history of moderate or high-energy VFs; v) history of surgical intervention on the spine; and vi) prolonged immobilization (more than 6 weeks). Out of the 109 enrolled patients, 84 had been already evaluated in previously published studies from our research group (14,15,16). Both surgically treated and medically treated patients were included.…”
Section: Subjectsmentioning
confidence: 99%
“…Fracture risk correlates with the activity of the disease and the presence of concomitant additional risk factors, such as hypogonadism (14,15,16). Nonetheless, it is still largely unclear as to whether GHR polymorphisms are implicated in this phenomenon and have an impact on skeletal fragility in acromegaly.…”
Section: Introductionmentioning
confidence: 99%